A sustained-release phospholipid-based phase separation gel loaded with berberine for treating rheumatoid arthritis - Peng, Xiong; Yang, Yuping; Guo, Chenqi; He, Qin; Li, Yan; Gong, Tao; Li, Jia (Frontiers in Pharmacology, 2023)
Berberine(BBR）has a long history of use in the treatment of Rheumatoid arthritis(RA)and is considered one of the most promising natural product for the treatment of RA. However, oral administration of berberine has low bioavailability and requires frequent administration, resulting in poor patient compliance. In this study, we developed a BBR-loaded phospholipid-based phase separation gel (BBR-PPSG) to achieve sustained drug release and long-term therapeutic effect. The stability of BBR-PPSG was verified and it was found that it can be stored for a long time. The pharmacokinetic study on rats and rabbits showed that BBR-PPSG not only achieved one-month of sustained release, but also significantly increased the area under the curve (AUC) by nearly 9-fold and prolonged the half-life (t1/2) by 10-fold. By constructing rat and rabbit models of RA, we also proved that BBR-PPSG administration once a month effectively alleviated joint swelling, and significantly reduce TNF-α levels in AIA rats and OIA rabbits. Histopathological analysis of rabbit joint sections revealed that after intra-articular injection of BBR-PPSG, the synovial cell layer remained intact, while in the model group, the synovial cells were significantly reduced and exhibited necrosis. MicroCT data analysis showed that the values of Tb.N and Tb.Sp in the BBR-PPSG group were significantly better than those in the model group (P < 0.05). This study addressed the limitations of frequent administration of BBR by developing a phospholipid-based phase separation gel system for berberine delivery, achieving long-term sustained release. The BBR-PPSG demonstrated good biocompatibility, simple preparation and excellent stability, thus holding potential as a novel pharmaceutical formulation for RA treatment.